2006
DOI: 10.1038/sj.ejcn.1602469
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns in the Southampton Women's Survey

Abstract: Objective: Dietary pattern analysis is receiving increasing attention as a means of summarizing the multidimensional nature of dietary data. This research aims to compare principal component analysis (PCA) and cluster analysis using dietary data collected from young women in the UK. Design: Diet was assessed using a 100-item interviewer-administered food frequency questionnaire. PCA and cluster analysis were used to examine dietary patterns. Setting: Southampton, UK. Subjects: A total of 6125 non-pregnant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
141
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(154 citation statements)
references
References 41 publications
(54 reference statements)
13
141
0
Order By: Relevance
“…Similar results have also been presented in other adult studies (42)(43)(44)(45) . Arrkola et al (2008) reported dietary patterns in relation to dietary intakes in 3730 pregnant women and identified seven dietary patterns, with energy intake found to be positively correlated with the 'healthy', 'fast food', 'traditional bread', 'traditional meat' and 'coffee' patterns.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results have also been presented in other adult studies (42)(43)(44)(45) . Arrkola et al (2008) reported dietary patterns in relation to dietary intakes in 3730 pregnant women and identified seven dietary patterns, with energy intake found to be positively correlated with the 'healthy', 'fast food', 'traditional bread', 'traditional meat' and 'coffee' patterns.…”
Section: Discussionsupporting
confidence: 91%
“…Previous work exploring these associations in relation to estimated nutrient intakes, although still limited, has primarily been in adults (42)(43)(44)(45) . To our knowledge, only one UK study has examined the associations between dietary patterns and nutrient intakes in children.…”
Section: Discussionmentioning
confidence: 99%
“…processed meat, confectionery and high-energy beverages (23) . The Osaka Maternal and Child Health Study in Japan reported three dietary patterns assessed by cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…All women were visited at home to obtain information on diet and lifestyle, and anthropometric measurements of body composition were taken. Between April 1998 and June 2000 (Crozier et al, 2006), 6129 women were interviewed. These women were living in the Western part of Southampton, and represent 75% of those women who could be contacted.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously described the two most important dietary patterns of women in the SWS (Crozier et al, 2006). Given that little is known about the stability of diet in young women, we examined the stability of these patterns over a two-year period in a subset of the women, and investigated factors that influence this stability.…”
Section: Introductionmentioning
confidence: 99%